2008
DOI: 10.1198/004017008000000280
|View full text |Cite
|
Sign up to set email alerts
|

Practical Design of Generalized Likelihood Ratio Control Charts for Autocorrelated Data

Abstract: Control charts based on Generalized Likelihood Ratio (GLR) tests are attractive from both a theoretical and practical point of view. In particular, in the case of an autocorrelated process, the GLR test uses the information contained in the time-varying response after a change and, as shown by Apley and Shi, is able to outperfom traditional control charts applied to residuals. In addition, a GLR chart provides estimates of the magnitude and the time of occurrence of the change. In this paper, we present a prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…An extension of the proposed MFPCA-based method to the non-normal or autocorrelated case could be a worthwhile and necessary future contribution to the existing multivariate Phase I methods (Capizzi and Masarotto 2008;Bell et al 2014). …”
Section: Concluding Remarks and Future Workmentioning
confidence: 96%
“…An extension of the proposed MFPCA-based method to the non-normal or autocorrelated case could be a worthwhile and necessary future contribution to the existing multivariate Phase I methods (Capizzi and Masarotto 2008;Bell et al 2014). …”
Section: Concluding Remarks and Future Workmentioning
confidence: 96%
“…We found that an efficient approach for the computation of consists in using the Polyak-Ruppert stochastic approximation algorithm [16,20]. In particular, our implementation is based on the recommendations given by Capizzi and Masarotto [3]. …”
Section: An Adaptive Cuscore Control Chartmentioning
confidence: 99%
“…In this context, three alternative approaches can be used to address the design issue: i) modifying decision intervals: control limits of classical control charts are widened to account for the variability in the sampling distribution of the estimates; see for example Jones [13] and Capizzi and Masarotto [3] for independent and autocorrelated data, respectively;…”
Section: Introductionmentioning
confidence: 99%
“…Observe, however, that when there is a nonnegligible uncertainty on the system matrices, the suggested detection algorithm may be designed using the bootstrap based methodology described in Capizzi & Masarotto [13], [14].…”
Section: A Frameworkmentioning
confidence: 99%